PENENTUAN NILAI SUSEPTIBILITAS DAN UKURAN PARTIKEL MAGNETIK PASIR ALAM LOGAS KABUPATEN KUANTAN SINGINGI MENGGUNAKAN VARIASI UKURAN BALL MILLING - Azura Royka; Erwin Amiruddin (Universitas Riau, 2021)
Magnetic properties and morphology of natural sand has been carried out in Logas Village, Kuantan Singingi Regency have been determined. Iron sand samples were processed using iron sand separator (ISS) prior to ball milling for separating between magnetic and non magnetic particles. The product of ISS was milled for 90 hours using ball milling first step method with milling ball size of 1.5 cm. Themagnetic and non-magnetic particles of ball milling products were separated using Neodymium Iron Boron (NdFeB) magnet. The product of ball milling first step then was milled for another 30 hours with milling ball size of 0.5 cm and 0.7 cm. The susceptibility and mass susceptibility were determined based on magnetic induction of a selenoid measured using Probe Magnetic Pasco PS-2162. The composition of Logas natural sand was measured using x-ray fluorescence spectroscopy (XRF). The morphology of the magnetic particles are determined using scanning electron microscope (SEM). The results showed that the particle size of natural sand for 90 hours + 30 hours milling displays the particle sizes from 100 µm to 800 µm. As for the particle size of the samples synthesized with 90 hours + 30 hours for 0.7 cm milling ball size, the particles are almost evenly distributed, which is about 5 µm to 100 µm. The content of Fe and Ti in the sample has increased while for Si has decreased. Mass susceptibility increases with increasing ball milling time and ball milling size.